Scaffold fabrication technologies and structure/function properties in bone tissue engineering - Collins, Maurice N. (2021)
Bone tissue engineering (BTE) is a rapidly growing field aiming to create a biofunctional tissue that can integrate and degrade in vivo to treat diseased or damaged tissue. It has become evident that scaffold fabrication techniques are very important in dictating the final structural, mechanical properties, and biological response of the implanted biomaterials. A comprehensive review of the current accomplishments on scaffold fabrication techniques, their structure, and function properties for BTE is provided herein. Different types of biomaterials ranging from inorganic biomaterials to natural and synthetic polymers and related composites for scaffold processing are presented. Emergent scaffolding techniques such as electrospinning, freezeâ drying, bioprinting, and decellularization are also discussed. Strategies to improve vascularization potential and immunomodulation, which is considered a grand challenge in BTE scaffolding, are also presented.